In vitro evaluation of bioremediation capacity of a commercial probiotic, Bacillus coagulans, for chromium (VI) and lead (II) toxicity - Pranoti Belapurkar; Pragya Goyal; Anand Kar (Wolters Kluwer Medknow Publications, 2016)
Introduction: The bioaccumulation of heavy metals including chromium (VI) (Cr (VI)) and lead (II) (Pb (II)) causes fatal toxicity in humans. Some naturally occurring bacterial genera such as Bacillus and Pseudomonas help in bioremediation of these heavy metals and some of the species of Bacillus are proven probiotics. However, no study has been conducted on Bacillus coagulans, which is a proven probiotic species of genus Bacillus. Objectives: The primary objective of the present study was to assess the potential of a proven probiotic, B. coagulans, marketed as "Sporlac-DS," to survive in the presence of Cr (VI) and Pb (II) and its ability to reduce its concentration in vitro. Materials and Methods: The Minimum inhibitory concentration (MIC) of the organism for Cr (VI) and Pb (II) was determined followed by its biochemical and morphological characterization. Its antibiotic sensitivity and probiotic efficacy were assessed. Further, its bioremediation capacity was observed in vitro by determining the residual Cr (VI) and Pb (II) concentration after 72 h. Results: B. coagulans could tolerate up to 512 ppm concentration of Cr (VI) and had an MIC of 128 ppm for Pb (II). After 72 h, the organism reduced 32 ppm Cr (VI) and 64 ppm Pb (II) by 93% and 89%, respectively. When B. coagulans was studied before and after growing on Cr (VI) and Pb (II) for 24 h, an increase was seen in sensitivity toward the tested antibiotics whereas no change was observed in morphological and biochemical characters. It also showed no change in their bile and acid tolerance, indicating that it retains its probiotic efficacy. Conclusion: The tested probiotic B. coagulans may have a potential role in bioremediation of Cr (VI) and Pb (II), in vivo.